Synthesis, determination, and bio-application in cellular and biomass-bamboo imaging of natural cinnamaldehyde derivatives - Yang, Jinlai; Guo, Rencong; Yang, Huimin; Wu, Liangru (Frontiers in Bioengineering and Biotechnology, 2022)
Cinnamon essential oil (CEO) is the main ingredient in the renewable biomass of cinnamon, which contains natural cinnamaldehyde. To valorize the value of cinnamaldehyde, two simple and useful compounds (1 and 2) from CEO were synthesized using a Schiff-base reaction and characterized by infrared spectra (IR), nuclear magnetic resonance (NMR), and high-resolution mass spectrometry (HRMS). Compound 1 was used to confirm the presence of Fe3+ and ClO- in solution, as well as compound 2. Using fluorescence enhancement phenomena, it offered practicable linear relationship of 1’s fluorescence intensity and Fe3+ concentrations: (0–8.0×10-5 mol/L), y=36.232x+45.054, R2=0.9947, with a limit of detection (LOD) of 0.323 μM, as well as compound 2. With increasing fluorescence, F404/F426 of 1 and the ClO- concentration (0–1.0×10-4 mol/L) also had a linear relationship: y=0.0392x+0.5545, R2=0.9931, LOD=0.165 μM. However, the fluorescence intensity of 2 (596 nm) was quenched by a reduced concentration of ClO-, resulting in a linear. In addition, compounds 1 and 2 were used to image human astrocytoma MG (U-251), brain neuroblastoma (LN-229) cells, and bamboo tissue by adding Fe3+ or ClO-, with clear intracellular fluorescence. Thus, the two compounds based on CEO could be used to dye cells and bamboo tissues by fluorescence technology.